Resin microtensile bond strength to feldspathic ceramic: Hydrofluoric acid etching vs tribochemical silica coating - Pelógia, Fernanda [UNESP]; Valandro, Luiz Felipe; Brigagão, Vinicius; Neisser, Maximiliano Piero; Bottino, Marco A. [UNESP] (My University, 2007)
This study aimed to compare the microtensile bond strength of resin cement to alumina-reinforced feldspathic ceramic submitted to acid etching or chairside tribochemical silica coating. Ten blocks of Vitadur-α were randomly divided into 2 groups according to conditioning method: (1) etching with 9.6% hydrofluoric acid or (2) chairside tribochemical silica coating. Each ceramic block was luted to the corresponding resin composite block with the resin cement (Panavia F). Next, bar specimens were produced for microtensile testing. No significant difference was observed between the 2 experimental groups (Student t test, P> .05). Both surface treatments showed similar microtensile bond strength values.
Keywords: aluminum silicate; feldspar; Panavia Fluoro; Panavia-Fluoro; potassium derivative; resin; resin cement; silane derivative; silicon dioxide; unclassified drug; comparative study; dental acid etching; dental bonding; dental care; dental surgery; methodology; tensile strength; tooth prosthesis; Acid Etching, Dental; Air Abrasion, Dental; Aluminum Silicates; Composite Resins; Dental Bonding; Dental Porcelain; Dental Stress Analysis; Potassium Compounds; Resin Cements; Silanes; Silicon Dioxide; Tensile Strength